The guncle abroad ebook - Rowley, Steven (The Guncle, 2024)
AN INSTANT USA TODAY BESTSELLER An Indie Next Pick Patrick O'Hara is called back to his guncle duties . . . This time for a big family wedding in Italy. Patrick O’Hara is back. It’s been five years since his summer as his niece Maisie and nephew Grant’s caretaker after their mother’s passing. The kids are back in Connecticut with their dad, and Patrick has relocated to New York to remain close by and relaunch his dormant acting career. After the run of his second successful sit-com comes to a close, Patrick feels on top of the world . . . professionally. But some things have had to take a back seat. Looking down both barrels at fifty, Patrick is single again after breaking things off with Emory. But at least he has a family to lean on. Until that family needs to again lean on him. When Patrick's brother, Greg, announces he’s getting remarried in Italy, Maisie and Grant are not thrilled. Patrick feels drawn to take the two back under his wing. As they travel through Europe on their way to the wedding, Patrick tries his best to help them understand love, much as he once helped them comprehend grief. But when they arrive in Italy, Patrick is overextended managing a groom with cold feet; his sister, Clara, flirting with guests left and right; a growing rivalry with the kids’ charming soon-to-be-launt (lesbian aunt), and two moody young teens trying to adjust to a new normal, all culminating in a disastrous rehearsal dinner. Can Patrick save the day? Will teaching the kids about love help him repair his own love life? Can the change of scenery help Patrick come to terms with finally growing up? Gracing the page with his signature blend of humor and heart, Steven Rowley charms with a beloved story about the complicated bonds of family, love, and what it takes to rediscover yourself, even at the ripe age of fifty.